How to Increase Foreign Direct Investment Inflows in OIC Countries: A Green Economy Model - Azzaki, Muhammad Adnan (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2023)
OIC countries face the challenge of attracting Foreign Direct Investment (FDI) while ensuring sustainable economic growth. In practice, traditional investment strategies ignore the role of environmental policies and governance in investor decision-making. This study aims to determine how green economic policies and institutional quality can influence FDI inflows in OIC countries to promote economic resilience and sustainability. This research uses explorative qualitative methods with several case studies to assess the relationship between governance, economic policy, and environmental sustainability. The results of this study suggest that strong institutions, transparency, and well-structured green policies can increase investor confidence. In addition, countries with stable political conditions, anti-corruption measures, and regulatory availability can attract more FDI, especially in the green sector. However, inefficient governance, environmental degradation, and inconsistent policies hinder investment in many OIC countries. This study implies that the OIC Government should strengthen the institutional framework, promote sustainable economic policies, and create a stable business environment. In addition, investing in green infrastructure and encouraging private sector involvement in environmentally friendly industries will increase FDI and drive long-term economic growth.